(untitled) (Research, Society and Development, 2025)
Objective: The present study aimed to evaluate the sleep quality of the professors of a private university in the municipality of Cascavel, Paraná/Brazil, based on the fact that sleep is a physiological mechanism of paramount importance for human metabolism, as it has an impact on the various functions performed by the body. Since the impairment of the sleep-wake cycle from external occasions or environmental factors, one of them being work, results in the triggering of sleep disorders, negatively impacting health. Methodology: Cross-sectional and quantitative-qualitative research with descriptive analysis and non-probalistic convenience sampling, carried out between March and June 2025 with 28 professors from the University of Paranaense (UNIPAR), based on the application of online questionnaires, including the Morning-Evening Identification (IMV) and the Epworth Sleepiness Scale (ESS). Results: Most teachers do not have excessive daytime sleepiness (75%), however, factorssuch as extensive workload, overweight (mean BMI of 26.94 kg/m²), use of electronic devices before bedtime (92.9%), and regular consumption of medications (53.6%) indicate risks to sleep quality. In addition, influences of marital status, multiple professional functions and divergent chronotypes in relation to working hours were identified. Conclusion: Although the data do not indicate an alarming prevalence of sleep disorders, there are relevant signs of impairment of the quality of night rest among teachers. These findings reinforce the importance of institutional measures aimed at promoting workers’ health, with a focus on sleep hygiene, adequacy of the workload, and psychosocial support.